Application of the ultrasound-guided double-screen contrast method in the standardized teaching and training of resident doctors in femoral vein puncture - Zhang, Yunshui; Li, Jin; Sun, Yaying; Liu, Tao; Guo, Wenmin; Ban, Weiwei; Ma, Yujie (Frontiers in Cardiovascular Medicine, 2023)
Objective The aim of this study was to investigate the advantages of the double-screen contrast method compared with the short-axis ultrasound display method for teaching ultrasound-guided femoral vein puncture during the standardized training of resident doctors. Methods Sixty resident doctors undergoing standardized training were randomly divided into a test group (short–long axis switching double-screen contrast, n = 30) and a control group (n = 30). These two groups of physicians underwent teaching and training of ultrasound-guided femoral vein puncture, and the success rate of the first puncture attempt, the total catheterization time, and any accidental femoral artery punctures were recorded and compared between the two groups. Results The success rate of the first puncture attempt in the test group was significantly higher than that in the control group (P < 0.05). In the control group, two doctors accidentally punctured the artery, while in the test group, no arterial punctures occurred. The puncture time for the test group was longer than for the control group (P < 0.05). Conclusion In the standardized training of ultrasound-guided femoral vein puncture for resident doctors, the double-screen contrast method has significant advantages. It enables resident doctors to quickly understand and apply the technique, so it is worth making this the method of choice.